Livestock Assets, Livestock Income and Rural Households : Cross-Country Evidence from Household Surveys - Pica-Ciamarra, Ugo (World Bank, Washington, DC, 2014)
This paper investigates the livestock asset positions of rural households and the contribution of livestock to their income in 12 developing countries. It draws on the FAO Rural Income Generating Activities (RIGA) database, which allows cross-country comparisons of household surveys. The majority of rural households keep livestock; the rural poor, defined as those living in rural areas and belonging to the bottom expenditure quintile, are more likely to keep livestock than those in higher quintiles; there are minor differences in herd composition between households, and the contribution of livestock to total income is overall small, with no significant differences across households.